THE CASE OF DESTRUCTIVE APPENDICITIS PREGNANT WITH COMPLICATED OBSTETRICAL PATHOLOGY - A. G. Khasanov; I. A. Zhuravlev; F. F. Badretdinova; D. C. Mamedova (Акушерство, гинекология и репродукция)
Complication of pregnancy acute appendicitis creates complex obstetric and surgical situation. Additional difficulties occur when acute surgical pathology occurs against a background of severe obstetric pathology for longer periods of pregnancy. The cases of acute appendicitis on the background of severe obstetric pathology in the form of a Central previa and true increment of the placenta in multiple pregnancies described in the literature. Therefore this case is actual.